PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI KELAS IV SD - Yogi Prasetyo; Elly's Mersina Mursidik; Winarno Winarno (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2023)
This research was conducted because of the low learning outcomes of fourth grade students at SD Negeri 1 Sedeng, in learning mathematics the material is area and circumference of flat shapes. Based on the results of pre-cycle activities, out of 19 students, only 7 students completed. This study aims to determine the increase in student learning outcomes in mathematics by applying the Make a Match type cooperative learning model to the material area and circumference of a flat shape. The data analysis method used in this research is descriptive qualitative and descriptive quantitative. Data collection techniques used in this study are observation, interviews and tests. The results of the study show that the application of the Make a Match cooperative model can improve student learning outcomes. The increase in student learning outcomes can be seen from the average value of students, in the pre-cycle of 68.6 with a 37% mastery percentage increased in the first cycle to 75.5 with 68% completeness percentage. However, this percentage has not yet reached an indicator of research success so that it is continued in cycle II to increase to 87.8 with a completeness percentage of 79%. So it can be concluded that there was an increase in student learning outcomes in both cycles.